Histological classification of mesial temporal sclerosis - D. V. Dmitrenko; M. A. Stroganova; N. A. Shnaider; G. P. Martynova; K. A. Gazenkampf; A. V. Dyuzhakova; Yu. S. Panina (Неврология, нейропсихиатрия, психосоматика)
Mesial temporal sclerosis (MTS) is the most common histopathology occurring in patients with drug-resistant temporal lobe epilepsy. Over the past decades, there have been various attempts to classify the variants of hippocampal neuronal cell loss in relation to postoperative outcome. However, no consensus on the common international definition and classification of MTS has been reached. The article describes the modern histological classification based on a semiquantitative hippocampal cell loss model. The publications dealing with the histological classification of mesial temporal sclerosis are reviewed.